Projeto informacional e conceitual de uma máquina para aplicação localizada de fertilizantes em pomares - Bertoldi, Tiago Lopes (2013)
The growth of peach trees (Prunus L.) plays a major social and economic role in Rio Grande do Sul. In the year 2012 alone, 132,874 tons of peaches were produced in the State. This activity is largely performed on family run farms and involves a high number of farm workers, thus contributing to keeping families in rural areas. Basic machinery and tools are needed for the crop implementation. The peach tree is a plant that demands fertilization throughout its life cycle, and nutrient absorption is mainly carried out by its roots. Since the adsorption area is smaller than the deposition area performed by conventional equipment, there may be unnecessary waste in the fertilization of orchards, raising costs. There are technologies available in the marketplace today that could solve this problem; these are, however, still inaccessible to small and medium scale family farming. Thus, the aim of this study was to develop an informally and conceptually designed mechanical system for the purpose of using band placement or localized granular fertilizer application, directed to peach-growing family farmers needs. The methodology of the design is based on a phase model which has been divided into informational design, conceptual design, preliminary design and detailed design. This study developed the first two phases. The initial or informational design phase identified clients needs according the role they played within each phase of the life cycle of the product so as to establish the design specifications, including a total of 18 requirements. The scope of the problem was analyzed in the conceptual design phase, when three viable functional structures to meet the design specifications were established. Research using solution principles was performed and the most promising combinations were selected so as to choose the most adequate one. The scope of the problem was to apply granular fertilizer evenly on the target. This way, the most adequate functional structure to attend to the design needs was met. Four machine conceptions were obtained, one of which was selected.